Optical design of a short-wave infrared coded aperture snapshot spectral imager based on Offner–Wynne imaging spectrometer - Song, Chong; Zhou, Liang; Liu, Zhaohui; Jiang, Kai; Liu, Kai (Oficyna Wydawnicza Politechniki Wrocławskiej, 2022)
A calculation model to obtain the optimal combination of Offner–Wynne imaging spectrometer parameters to balance the RMS spot radius of the chief ray over the entire field is established. On the basis of the calculation model, an Offner–Wynne imaging spectrometer is designed, and then it is applied in a short-wave infrared coded aperture snapshot spectral imager (CASSI). The optical system of the short-wave infrared CASSI is designed by a combination method of independent design and integrated optimization. The spectral smile and spectral keystone of the optical system which operates in the 900–1700 nm band are respectively less than half a pixel. The focal length of the optical system is 1200 mm, the total optical system length is 775 mm, and its average spectral resolution is 16 nm. The optical system offers the advantages of excellent imaging quality, compact optical structure, high optical transmittance, reduced spectral smile and spectral keystone.
Optica Applicata, Vol. 52, 2022, nr 2, s. 143-161
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; Offner–Wynne imaging spectrometer; CASSI; short-wave infrared; optical design